Webinar Bagi Mahasiswa Baru 2021 "Sejarah dan Pemikiran H.O.S. Cokroaminoto" - Heri Kurnia (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
This Community Service, is carried out virtually in the form of online or webinars. This activity was organized by the Campus Academic Introduction committee, Cokroaminoto University of Yogyakarta in 2021. This webinar is a routine activity held every year, to introduce a campus environment for new students every year. This activity raised the theme "Historyand Thought of Cokroaminoto", which was carried out using a zoom platform.  The purpose of this webinars to get to know more closely the famous figure as well as the nation's teacher, H.O.S. Cokroaminoto, which gave the idea of Indonesia should be independent since 1912. Cokroaminoto helped raise the first national movement organization in Indonesia, the Islamic Trading Company which was established in 1905 with the founding figure H. Samanhudi. Cokroaminoto holds the title of teacher of the nation, because he has 3 famous students: Sukarno, Musso and Kartosuwiryo, all three of whom have different ideologies: Nationalists, Communists and Religious, as well as his three disciples also managed to color the journey of this nation, even more so during the old order. In the implementation of this webinar, it appears that the participation, enthusiasm and spirit of the participants, so that this webinar activity can be carried out properly and smoothly.